2011
DOI: 10.4141/cjps2010-004
|View full text |Cite
|
Sign up to set email alerts
|

Giant ragweed (Ambrosia trifidaL.) control in corn

Abstract: Twelve field trials (five with PRE and seven with POST herbicides) were conducted over a 4-yr period (2006Á2009) on various Ontario farms with heavy giant ragweed infestations (22 plants m (2) to determine the effectiveness of preemergence (PRE) and postemergence (POST) herbicides for the control of giant ragweed in corn. Atrazine, dicamba, dicamba/atrazine, isoxaflutole plus atrazine, mesotrione plus atrazine, saflufenacil, and saflufenacil/dimethenamid applied PRE provided 9Á52, 60Á80, 64Á83, 44Á77, 33Á80, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Reference [17] similarly reported unacceptable giant ragweed control of 9 to 52% 8 WAA with atrazine applied PP in corn. While the current study demonstrated good control for glyphosate plus mesotrione and atrazine applied PP, reference [18] reported only GR giant ragweed suppression from the same treatment.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [17] similarly reported unacceptable giant ragweed control of 9 to 52% 8 WAA with atrazine applied PP in corn. While the current study demonstrated good control for glyphosate plus mesotrione and atrazine applied PP, reference [18] reported only GR giant ragweed suppression from the same treatment.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
“…In other studies, reference [17] evaluated control of giant ragweed using various POST herbicides in corn and found dicamba/atrazine most effective, ranging from 87% to 94%, while atrazine control was as low as 46%. In dicamba-tolerant soybean, up to 100% control of GR giant ragweed has been reported for dicamba applied POST [19] and for sequential early-and late-POST dicamba applications [20].…”
Section: Postemergence Tank-mixesmentioning
confidence: 99%
See 1 more Smart Citation
“…While biotypes of Texas panicum expressing resistance to glyphosate have not been reported, biotypes of common ragweed resistant to glyphosate have been documented in several geographic regions of the US [15]. Dicamba alone or in combination with other herbicides can be effective in controlling common ragweed and other broadleaf weeds [16,17]. Dicamba and glufosinate applied to small common ragweed can control this weed effectively and can serve as alternatives to atrazine and glyphosate in corn [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate plus saflufenacil or saflufenacil/dimethenamid-p provided 46% to 91% and 47% to 93% control, respectively ( Table 4). Soltani et al [16] reported 45% to 80% and 53% to 63% control with saflufenacil at 75 g a.i. ha −1 and saflufenacil/dimethena- , respectively applied alone 4 weeks after corn emergence.…”
Section: Enhanced Burndownmentioning
confidence: 99%